Spatial temporal distribution of Aedes aegypti and of Aedes albopictus in São Paulo state, Brazil, 1986 to 2015 - Júnior, Dalton Pereira da Fonseca (2020)
To characterize the historical series of the number of cities infected by Aedes aegypti and by Aedes albopictus in the state of São Paulo (ESP), from 1986 to 2015. To analyze their seasonality, average temperatures, infestation indicators of each species, and to verify their spatial interdependence in Metropolitan Region of the Vale do Paraíba Paulista (RMVP). The data from entomological surveillance actions were obtained using the Breteau index (IB), from the database of the Superintendence of Control of Endemics (Sucen). The arithmetic means were calculated by month and year and, then, analyzed by the Wilcoxon test. The temperature maps were obtained at the National Institute of Meteorology (NIMET). [...]